Pancreatic Cancer: New Hopes for Early Detection and a Future Screening Tool? - El-Jurdi, Najla H; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Given the overall poor prognosis of patients with pancreatic cancer, there has always been an interest in early screening and primary prevention. An abstract presented in ASCO 2014 by Orlowski et al. introduced the potential use of an elevated serum procarboxypeptidase A (PCPA) and high ratios of PCPA to free carboxypeptidase A (FCPA) in enhancing the diagnostic efficacy of pancreatic cancer either alone or with CA19-9 (Abstract #4118). Image: Screening.